INFORMATION SYSTEM SECURITY USING THE DISCRETE COSINE TRANSFORM (DCT) METHOD - Sujarwo, Sujarwo (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Information system security is a crucial aspect in the digital era, especially for protecting sensitive data. One method to enhance data security is steganography, a technique for concealing information within digital media. This study analyzes the effectiveness of the Discrete Cosine Transform (DCT) method in digital image steganography. The research follows several stages, including literature review, system design, DCT implementation using MATLAB/Python, and performance evaluation based on Peak Signal-to-Noise Ratio (PSNR), Mean Squared Error (MSE), and Normalized Correlation (NC). Experimental results indicate that the DCT method achieves a high PSNR value (averaging above 40 dB) and a low MSE value, ensuring minimal image distortion after data embedding. Compared to the Least Significant Bit (LSB) method, DCT provides better resistance to visual analysis and is more suitable for images with transform-based compressions, such as JPEG. This study concludes that the DCT method is an effective steganography technique for enhancing information system security, despite challenges related to computational complexity and data embedding capacity. Future research may explore hybrid methods that combine DCT with other techniques to improve efficiency and robustness against various steganographic analysis attacks.